PATHOGENETIC FEATURES OF THE COURSE OF ANEMIA IN JUVENILE RHEUMATOID ARTHRITIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Anemia is one of the most common extra-articular manifestations in patients suffering from juvenile rheumatoid arthritis (JRA), with a reported prevalence ranging from 15 to 60%. It is well known that anemia in JRA is associated with higher disease activity, worse outcome parameters, and increased mortality [3]. The opinion of most researchers agrees that anemia of chronic disease (ACD) most often prevails in patients with JRA, with the combination of ACD and iron deficiency anemia (IDA) in second place, with the overall prevalence of anemia ranging from 30 to 70% [4]. In the absence of inflammation, serum ferritin, as an indicator of total body iron stores, is the most useful parameter for differentiating ACD from IDA [1,2,5]. Despite the huge amount of research in this direction, today the question of the pathogenesis and course of anemia in patients with juvenile rheumatoid arthritis remains open.